Evaluation the effect of hydro-alcoholic extract of Portulaca oleracea and estradiol on pain threshold in female mice - Khaled Keshavarzi; Mojtaba Moradi; Esmaeil Khoshnam; Alvand Alvandi; Mansour Safaei Pour Zamani; Mohamad Fatahi; Azim Baziar (Institue of Medicinal Plants, ACECR, 2017)
Background: There are many plant extracts which can modulate pain response. Also, studies represented modulatory effects of estradiol on pain. Objectives: The aim of the present study was to evaluate the effect of hydro alcoholic extract of Portulaca oleracea (purslane) and estradiol on pain threshold in female mice. Methods: In this experimental study, 90 female balb c mice were randomly divided into the control and experimental groups which receiving low, moderate and high doses of purslane extract, estradiol and their combination. Following intraperitoneal administration of the hormone or extract, pain threshold was measured using tail flick test, and acquired data have been analyzed using ANOVA. Results: Pain threshold was significantly increased after administration of moderate and high doses of purslane extract with comparing to the control group (P<0.005 and P<0.009, respectively). Also, the administration of moderate and high doses of estradiol caused significantly increasing of the pain threshold with comparing to the control group (P<0.009 and P<0.001, respectively). Finally, co-administration the low doses of estradiol and purslane extract and co-administration the high doses of estradiol and purslane extract resulted increasing of the pain threshold with compare to the control group, but there was not significant changed in comparing to the groups which received low doses of estradiol and extract. Conclusion: Present study showed that purslane seed extract and estradiol caused increasing of the pain threshold in the female mice. Hence, these results maybe demonstrate morphine-like effects of purslane extract and estradiol.